Watersheds – Functions and Management - Shukla Sanjay (EDIS)
The term watershed is often used in discussions about water quality or flood prevention, but most people do not really understand what a watershed is. The definition of a watershed is based on a concept with which everyone is familiar: “Water runs downhill.” A Watershed is a land area whose runoff drains into any stream, river, lake, and ocean. Watershed boundary is the divide separating one drainage area from another. Watersheds may be as small as the portion of a yard draining into a mud puddle or as large as the Mississippi River Basin, which drains 1.2 million square miles. Terms like catchment or drainage basin are also used to refer to watersheds. This document is ABE350, one of a series of the Department of Agricultural and Biological Engineering, UF/IFAS Extension. Original publication date April 2004.